Insect Diversity on Sugar Palm (Arenga pinnata Merr.) and Their Correlation with Abiotic Factors in Lintau Buo Utara District, West Sumatra Province - Sandy Miranda Pranata; Zahlul Ikhsan; Halimatus Syahdia Hasibuan (Universitas Trunojoyo Madura, 2026)
Sugar palm (Arenga pinnata Merr.) is a high-value commodity whose reproductive success depends heavily on insect-mediated pollination. However, empirical data regarding insect diversity and their activity patterns across different altitudinal gradients remain scarce. This study aimed to identify the diversity of pollinator and visitor insects and evaluate their correlation with abiotic factors across three altitude strata: 500–700 masl, 700–1000 masl, and 1000 masl in Lintau Buo Utara, West Sumatra. Using a survey method with purposive sampling, observations were conducted over four weeks utilizing malaise traps, yellow sticky traps, and visual counts. A total of 857 individuals were recorded, consisting of 712 pollinators (dominated by Apis, Vespa, Episyrphus, and Polyrhachis) and 145 visitors (including Aphrophora, Macroglossum, and Spodoptera). Ecological analysis revealed a moderate overall diversity index (H' = 2.04), with pollinators showing higher evenness (E = 0.92) compared to visitors (E = 0.89). The most optimal pollination activity was consistently observed at elevations of 700–1000 masl. Pearson correlation analysis demonstrated that rainfall and relative humidity were the primary environmental drivers, exhibiting significant and robust negative correlations with insect presence (r = -0.94, p 0.05 for rainfall; r = -0.64, p 0.05 for humidity), whereas air temperature showed a non-significant moderate influence (p 0.05). Furthermore, a perfect positive correlation was found between pollinator and visitor patterns (r = 1.00, p 0.01). These findings suggest that medium-altitude agroecosystems provide the most supportive microclimate for sugar palm pollinators, though high precipitation remains a critical limiting factor for their foraging efficiency.